2014
DOI: 10.1016/j.bbadis.2014.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resveratrol on mitochondrial function: Implications in parkin-associated familiar Parkinson's disease

Abstract: Mitochondrial dysfunction and oxidative stress occur in Parkinson's disease (PD), but the molecular mechanisms controlling these events are not completely understood. Peroxisome proliferator-activated receptor-gamma coactivator-1α (PGC-1α) is a transcriptional coactivator known as master regulator of mitochondrial functions and oxidative metabolism. Recent studies, including one from our group, have highlighted altered PGC-1α activity and transcriptional deregulation of its target genes in PD pathogenesis sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
169
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(180 citation statements)
references
References 69 publications
10
169
1
Order By: Relevance
“…Mitochondria are critical for ATP production, and many small molecules that activate AMPK, including metformin, resveratrol, berberine, and rotenone, have been shown to inhibit mitochondrial function (50)(51)(52)(53)(54). To produce ATP, ADP must enter the mitochondria through VDAC in the outer membrane and the adenine nucleotide transporter (ANT) in the inner membrane, be converted to ATP through oxidative phosphorylation, and then exit the mitochondria again through ANT and VDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are critical for ATP production, and many small molecules that activate AMPK, including metformin, resveratrol, berberine, and rotenone, have been shown to inhibit mitochondrial function (50)(51)(52)(53)(54). To produce ATP, ADP must enter the mitochondria through VDAC in the outer membrane and the adenine nucleotide transporter (ANT) in the inner membrane, be converted to ATP through oxidative phosphorylation, and then exit the mitochondria again through ANT and VDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory and that of others have demonstrated that the natural antioxidant resveratrol improves organ function following severe hemorrhage (23)(24)(25). Resveratrol has been shown to enhance mitochondrial function as well as biogenesis, and has been implicated in the extension of life span in several species (26)(27)(28)(29). However, determining the effect of resveratrol in reducing mortality or prolonging survival following hemorrhagic shock is important toward initiating clinical trials to use this agent as an adjunct to resuscitation fluid following severe hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence showed the improvement of mitochondrial respiratory capacities by RSV treatment. In fact, RSV activates SIRT1‐AMPK pathway and then induces PGC‐1alpha activity (Ferretta et al., 2014). PGC‐1alpha activation leads to mitochondrial biogenesis and amelioration of its function.…”
Section: Resveratrol and Diseasesmentioning
confidence: 99%